Transient Astrocytic Gq Signaling Underlies Remote Memory Enhancement - Iwai, Youichi; Ozawa, Katsuya; Yahagi, Kazuko; Mishima, Tsuneko; Akther, Sonam; Vo, Camilla Trang; Lee, Ashley Bomin; Tanaka, Mika; Itohara, Shigeyoshi; Hirase, Hajime (Frontiers in Neural Circuits, 2021)
Astrocytes elicit transient Ca2+ elevations induced by G protein-coupled receptors (GPCRs), yet their role in vivo remains unknown. To address this, transgenic mice with astrocytic expression of the optogenetic Gq-type GPCR, Optoα1AR, were established, in which transient Ca2+ elevations similar to those in wild type mice were induced by brief blue light illumination. Activation of cortical astrocytes resulted in an adenosine A1 receptor-dependent inhibition of neuronal activity. Moreover, sensory stimulation with astrocytic activation induced long-term depression of sensory evoked response. At the behavioral level, repeated astrocytic activation in the anterior cortex gradually affected novel open field exploratory behavior, and remote memory was enhanced in a novel object recognition task. These effects were blocked by A1 receptor antagonism. Together, we demonstrate that GPCR-triggered Ca2+ elevation in cortical astrocytes has causal impacts on neuronal activity and behavior.